1992
DOI: 10.2172/10120105
|View full text |Cite
|
Sign up to set email alerts
|

Comparative plant uptake and microbial degradation of trichloroethylene in the rhizospheres of five plant species-- implications for bioremediation of contaminated surface soils

Abstract: This report was prepared as an account of work sr_:)nsored by an agency of .. the United States Government. Neither the United States Government nor any agency therec_, nor any of their employees, makes any warranty, express or. I_ implied, or assumes any legal liability or responsibility for the accuracy, completeness, or usefulness of any information, apparatus, product, or process disclosed, or represents that its use would not infringe privately owned rights. Reference herein to any specific commercial pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 84 publications
0
8
0
Order By: Relevance
“…Recent results have been presented from an investigation in which water saturated with toluene at 26" C and 0.5 ml/L of 93 percent phenol in water were fed into separate 1.8 m long and 35 cm deep laboratory chambers containing soil with alfalfa growing at the surface [ZO, 12, 221. The ground water was sampled at four sampling wells (ports [1][2][3][4] which were located along the flow path of each chamber. Ports 1 and 2 were 33 cm and 66 cm from the inlet, respectively; ports 3 and 4 were 66 cm and 33 cm from the outlet, respectively.…”
Section: Transformation Of Soluble and Biodegradable Compoundsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent results have been presented from an investigation in which water saturated with toluene at 26" C and 0.5 ml/L of 93 percent phenol in water were fed into separate 1.8 m long and 35 cm deep laboratory chambers containing soil with alfalfa growing at the surface [ZO, 12, 221. The ground water was sampled at four sampling wells (ports [1][2][3][4] which were located along the flow path of each chamber. Ports 1 and 2 were 33 cm and 66 cm from the inlet, respectively; ports 3 and 4 were 66 cm and 33 cm from the outlet, respectively.…”
Section: Transformation Of Soluble and Biodegradable Compoundsmentioning
confidence: 99%
“…Ports 1 and 2 were 33 cm and 66 cm from the inlet, respectively; ports 3 and 4 were 66 cm and 33 cm from the outlet, respectively. The results presented in Tables [1][2][3][4] indicate that significant quantities of the toluene and phenol which enter are not present in the effluent. The results with toluene appear to indicate that microbial degradation occurs in the rhizosphere in the unsaturated zone.…”
Section: Transformation Of Soluble and Biodegradable Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regulated air flow was passed through a series of three gas-washing bottles for 30 minutes. Efficiency studies with Carbosorb in an identical experimental setup (Anderson 1991) showed that 70% of the 14002 released from combustion of the standard 14C-methyl methacrylate was trapped by Carbosorb. Therefore, data reported for 14002 in this study were corrected by this efficiency value.…”
Section: Trao Calibrationmentioning
confidence: 99%
“…Phytomanagement thus uses phytoremediation strategies to secure brownfield sites through revegetation, but also has the ambition to develop economic activities generating value chains in areas that were previously deprived of them (French et al 2006;Gerhardt et al 2009;Gomes 2012;Bert et al 2017;Dudai et al 2018). This has been a well-documented technique since the 1990s (Anderson and Walter 1992) and many studies have been conducted to identify suitable plant species that can both meet the requirement of risk management and be valorized through biomass production (e.g. heat generation or bioproducts) (Jiang et al 2015(Jiang et al , 2022Ciadamidaro et al 2019;Padoan et al 2020;Moreira et al 2021;Guidi Nissim and Labrecque 2021).…”
Section: Introductionmentioning
confidence: 99%